Analytical Techniques for a Numerical Solution of the Linear Volterra Integral Equation of the Second Kind - M. I. Berenguer; D. Gámez; A. I. Garralda-Guillem; M. Ruiz Galán; M. C. Serrano Pérez (Abstract and Applied Analysis)
In this work we use analytical tools—Schauder bases and Geometric Series theorem—in order to develop a new method for the numerical resolution of the linear Volterra integral equation of the second kind.